Pigs and poultry in the tropics : utilization of local feed resources - Preston, T R (Technical Centre for Agricultural and Rural Cooperation WageningenNL, 1987)
Presents alternative approaches to poultry production as a means of replacing conventional intensive methods which have proved unsuitable for ACP countries and rely on costly imported feeds. Proposes the use of locally available resources. Emphasizes need to reduce dependence on imports while increasing the value of national products, in conformity with the aspirations of ACP countries. Topics discussed include inter alia, nutritional characteristics of tropical feed, and feeding systems using non-conventional feeds.